2012
DOI: 10.1186/2045-4015-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Progress in palliative care in Israel: comparative mapping and next steps

Abstract: Palliative care was established rapidly in some countries, while in other countries its establishment has taken a different trajectory. This paper identifies core steps in developing a medical specialty and examines those taken by Israel as compared with the US and England for palliative care. It considers the next steps Israel may take.Palliative care aims to provide quality of life for those with serious illnesses by attending to the illness-prompted physical, mental, social, and spiritual needs of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
(38 reference statements)
1
28
0
1
Order By: Relevance
“…The current study rate was higher than 12% of home care patients reported previously and 10% reported in hospitals, nursing homes, and assisted living in the United States. Cultural, ethical, religious, and administrative considerations influence the decision to insert a feeding tube . There are no Israeli Ministry of Health guidelines regarding the use of enteral feeding in individuals with dementia in the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study rate was higher than 12% of home care patients reported previously and 10% reported in hospitals, nursing homes, and assisted living in the United States. Cultural, ethical, religious, and administrative considerations influence the decision to insert a feeding tube . There are no Israeli Ministry of Health guidelines regarding the use of enteral feeding in individuals with dementia in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural, ethical, religious, and administrative considerations influence the decision to insert a feeding tube. [36][37][38] There are no Israeli Ministry of Health guidelines regarding the use of enteral feeding in individuals with dementia in the community. In Israeli culture, the sanctity of human life is a central value, and human life is deemed of infinite value.…”
Section: Discussionmentioning
confidence: 99%
“…Dental care for adults, optometry, and home care are generally excluded, although the National Insurance Institute does provide some funding for home care, dependent on need. Limited palliative and hospice services are included in the NHI benefits package as well (Bentur et al, 2012).…”
Section: What Is Covered?mentioning
confidence: 99%
“…Moreover, oncologists in our study reported that, in their view, distress was a "normal" part of the cancer trajectory, akin to other symptoms of cancer treatment such as hair loss, and was part and parcel of receiving a cancer diagnosis. While distress may be one response to cancer and the treatment trajectory, there is substantial evidence that psychosocial care (Andersen et al, 2004;Breitbart et al, 2015;Carlson et al, 2012;Faller et al, 2013;Fann et al, 2012;Jacobsen & Wagner, 2012;Li et al, 2012;Stagl et al, 2015) and adequate control of physical symptoms including pain relief (Bentur, Emanuel, & Cherney, 2012;Ferrell et al, 2016;Gans et al, 2012;Temel et al, 2010;Zimmermann et al, 2014) can substantially eliminate the distress associated with cancer. Appropriate systematic screening of distress in cancer patients is essential to providing the best quality of care.…”
Section: Differentiating Between "Normal" Distress and Psychopatholmentioning
confidence: 99%